2013
DOI: 10.1097/mat.0b013e3182816cb7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Functional Status Measures of Heart Failure Patients With Mechanical Assist Devices

Abstract: Continuous-flow left ventricular assist devices (cfLVADs) have been proven safe and effective for bridge-to-transplant and destination therapy (DT) in patients with advanced heart failure. However, the fixed pump speed of these devices may lack response to activity and oxygen demand, thereby limiting exercise tolerance. The objective of this observational study was to describe exercise capacity as measured by peak oxygen consumption (peak VO2) that may be expected during support with a cfLVAD. Peak VO2 was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 17 publications
1
42
1
1
Order By: Relevance
“…[16][17][18] Two small studies with paired pre-and postimplant VO 2 showed similarly small increases in VO 2 max after 3-6 months of support. 19,20 Recently, Nahumi et al 21 2.0 ± 0.7 Mixed venous oxygen saturation (%) 50.8 ± 12.8 Right ventricular stroke-work index (g/m 2 /beat) 6.9 ± 3.3 Right ventricular failure risk score, n (%) ‡ ≤3 31 (89) 4-5 2 (6) ≥5. 5 2 (6) Plus-minus values are mean ± SD.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Two small studies with paired pre-and postimplant VO 2 showed similarly small increases in VO 2 max after 3-6 months of support. 19,20 Recently, Nahumi et al 21 2.0 ± 0.7 Mixed venous oxygen saturation (%) 50.8 ± 12.8 Right ventricular stroke-work index (g/m 2 /beat) 6.9 ± 3.3 Right ventricular failure risk score, n (%) ‡ ≤3 31 (89) 4-5 2 (6) ≥5. 5 2 (6) Plus-minus values are mean ± SD.…”
Section: Discussionmentioning
confidence: 99%
“…(18) Mean peak VO 2 at 3 months increased to a range from 12.66 to 18.3 mL/kg/min across several studies. (18,2224) By 6 months, peak VO 2 ranged from 12.7 to 18.7 mL/kg/min. (21,2426) Percentage of predicted norms reflected these increases with percentages increasing from 48–61% at 1 month to 42–66% at 12 months.…”
Section: Describing Functional Progressmentioning
confidence: 99%
“…The overriding therapeutic goal of LVAD implantation is to ensure patient survival and guarantee preservation of organ function (2). However, when patients become permanently dependent on the system, a return to everyday life and restoration of an acceptable quality of life acquire crucial significance.…”
mentioning
confidence: 99%